Bantuan Sosial Sembako dan Bantuan Sosial Tunai - Fadilah, Rahmi (Jurnal El-Thawalib, 2021)
Direct Cash Assistance is a policy issued by the government which has a specific purpose and reason primarily to eradicate poverty. However, in Mompang Julu Village, North Panyabungan District, Mandailing Natal Regency, there are still many problems due to the unfair and unequal distribution of direct cash assistance. The distribution of aid lacks transparency, which causes a commotion. From this problem the author wants to know how to implement the Decree of the Minister of Social Affairs Number 54/Huk/2020 concerning the Implementation of Basic Food Social Assistance and Cash Social Assistance in Handling the Impact of Corona Virus Disease 2019 in Mompang Julu Village, Panyabungan District North Mandailing Natal Regency, what are the supporting and inhibiting factors, and how is the Fiqh Siyasah Review of the Decree of the Minister of Social Affairs Number 54/Huk/2020 concerning the Implementation of Basic Food Social Assistance and Cash Social Assistance in Handling the Impact of Corona Virus Disease 2019 in Mompang Julu Village, North Panyabungan District Christmas Mandailing. The type of research used in this study isfield research, using qualitative descriptive analysis methods, namely describing phenomena or events in the field. The data collection instrument used consisted of interviews, observations, and documentation. The results of this study are that the implementation of the Minister of Social Affairs Decree Number 54/HUK/2020 concerning the Implementation of Basic Food Social Assistance and Cash Social Assistance in Handling the Impact of the 2019 Corona Virus Disease in Mompang Julu Village, North Panyabunga Subdistrict, did not run smoothly and well, then the supporting factors were because the emergence of socialization of the Village Fund BLT expenditure program, while the inhibiting factor is the lack of firmness of an implementer's attitude, as for the view of the fiqh siyasah review that in the management of state finances based on the distribution of state expenditures and expenditures it must be fair but what the relevant authorities are not fair.